Business Behavior Model And Business Performance Of Areca Nut Farmers In Tanjung Jabung Timur District And Tanjung Jabung Barat - Tona Aurora Lubis; Asep Machpudin; Sigit Indrajaya; Ahmad Nur Budi Utama; Muhammad Haris Saputra; Maryati Ningsih (Citakonsultindo, 2025)
In its development, the Pinang commodity is a leading regional commodity in Jambi Province in general, and Tanjabtim and Tanjabbar districts in particular. Tanjung Jabung Timur and Tanjung Jabung Barat districts are the largest and best producers of Pinang commodities in Jambi Province. This makes Pinang one of the leading export products of the district. So that Pinang is widely used by the community as a source of livelihood both in the form of buying and selling businesses and field investments. As a leading commodity, the business behavior and business performance of Pinang farmers are needed to develop this Pinang business or business in the future. Research on the business behavior and business performance of Pinang farmers has never been studied before. This study has the ultimate goal of formulating a Model of Business Behavior and Business Performance of Pinang Farmers in Tanjung Jabung Timur and Tanjung Jabung Barat Districts. This study applies a combination research (mixed method) with the Sequential Exploratory Design type, namely the initial stage using qualitative research with NVivo software, then the second stage using quantitative research with SmartPLS software. The results of this study conclude that Pinang farmers consist of: hereditary pinang farmers and